Academia versus Realidade: Estagnação ou Solidez? - Pecequilo, Cristina Soreanu (Meridiano 47 - Journal of Global Studies, 2017)
The area of International Relations in Brazil has undergoing several transformations in the last forty years, presenting phases of enlargement and growth, as well as with significant challenges in the teaching and research field. The goal of this article is to analyze which are the advancements and setbacks of the area, by comparing the practical and the academic reality, evaluating existing trends of stagnation and strengthening.